New NHS Prehospital Major Incident Triage Tool: from MIMMS to MITT. Issue 11 (16th October 2022) - Vassallo, James; Moran, Chris G; Cowburn, Philip; Smith, Jason
Abstract : Triage is a key principle in the effective management of major incidents and is the process by which patients are prioritised on the basis of their clinical acuity. However, work published over the last decade has demonstrated that existing methods of triage perform poorly when trying to identify patients in need of life-saving interventions. As a result, a review of major incident triage was initiated by NHS England with the remit to determine the optimum way in which to triage patients of all ages in a major incident for the UK. This article describes the output from this review, the changes being undertaken to UK major incident triage and the introduction of the new NHS Major Incident Triage Tool from the Spring of 2023.